2020
DOI: 10.3892/mco.2020.2113
|View full text |Cite
|
Sign up to set email alerts
|

Two primary cancers: Primary squamous cell carcinoma with extensive ichthyosis uteri and cervical endometrioid carcinoma: A case report

Abstract: Squamous cell carcinoma of the endometrium is extremely rare, accounting for approximately 1% of uterine body malignancies. The present report describes a case of squamous cell carcinoma of the uterine body arising from ichthyosis due to persistent pyometra. A 68-year-old Japanese woman, gravida 1 para 1, was referred to the Gynecological Department of Tokyo Women's Medical University, due to watery brown vaginal discharge which had persisted for 10 days. Pelvic magnetic resonance (MRI) imaging revealed a tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Currently, there are only a few cases that report the cooccurrence of ichthyosis uteri with keratinizing squamous metaplasia, [8,9] squamous cell carcinoma, [3] and endometrioid carcinoma. [4,10,11]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are only a few cases that report the cooccurrence of ichthyosis uteri with keratinizing squamous metaplasia, [8,9] squamous cell carcinoma, [3] and endometrioid carcinoma. [4,10,11]…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are only a few cases that report the cooccurrence of ichthyosis uteri with keratinizing squamous metaplasia, [8,9] squamous cell carcinoma, [3] and endometrioid carcinoma. [4,10,11] Only 2 cases of endometrial cancer with TCD have been reported in the literature. [12,13] The TCD were highly cellular and covered by multilayered polygonal cells with abundant pale eosinophilic cytoplasm, well-defined cell borders, and round to ovoid nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…Among the reported cases of PSCCE, some were P16-negative, and most were ER and PR-negative. [4,9,10,16,18] According to Hopkins et al, ER and PR expression may be limited. [10] Most studies have demonstrated a mutation in the p53 tumor suppressor gene, and Ki-67 was reported with a high labeling index, indicating the aggressive and malignant nature of the lesion.…”
Section: Discussionmentioning
confidence: 99%